Analisa Faktor yang Berpengaruh Terhadap Keputusan Petani dalam Diversifikasi Usaha Tani - Harahap, Ahmad Alifsyah; Tambun, Immanuel Figo; Siregar, Fachry Pahlevi; Al-Syafiq, M. Zaky; Arika, Tadzkia Dina (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Farm enterprise diversification is an important strategy to enhance the economic resilience of farming households and reduce the risk of farming failures. This article discusses the factors influencing farm diversification decisions, including education, farming experience, availability of capital, family labor, and local social and cultural norms. Higher education promotes the adoption of agricultural innovations and technologies, while long-term farming experience enhances adaptability and risk management. Capital and access to financing, such as the People's Business Credit (KUR) program, strengthen farmers’ willingness to venture into new commodities. Moreover, the availability of family labor increases production efficiency, and supportive social norms facilitate the acceptance of diversification innovations. The findings indicate that farm diversification in Indonesia results from the synergy between economic, demographic, and socio-cultural factors.